PERFORMANCE, EFFORT EXPECTANCY AND BUSINESS EDUCATION STUDENTS’ BEHAVIORAL INTENTION TOWARDS ONLINE LEARNING IN BAUCHI STATE, NIGERIA - Garba, Sankira Babayo; Inuwa, Umar; Ibrahim, Adamu (Kashere Journal of Management Sciences, 2024)
This study investigates the influence of performance and effort expectancy on Business Education students’ behavioral intention towards online learning in Bauchi State, Nigeria. Employing a quantitative survey design, structured questionnaires were distributed to 300 randomly selected final-year business education students across four tertiary institutions in Bauchi state. Multiple regression analysis was used to test the hypotheses. The findings reveal that both performance expectancy and effort expectancy significantly influence Business Education students’ behavioral intention towards online learning in Bauchi State. These factors collectively shape students' attitudes and willingness to engage in online learning platforms. The study recommends that policymakers, institutions, and educators in Bauchi State prioritize the development and implementation of training programs aimed at enhancing students' performance expectancy and effort expectancy in online learning. Additionally, investing in improving technological infrastructure, such as reliable internet connectivity and user-friendly interfaces, is essential to facilitate seamless online learning experiences. Addressing these recommendations can create an environment conducive to fostering positive attitudes and intentions toward online learning among Business Education students in Bauchi State.